Zero-Trust Architecture Adaptation for Post-Quantum Cryptography: Implementation Roadmap for Critical Infrastructure - Nurhaliza, Nurhaliza; Darmawan, Adichandra Febryana Yuscatama (Al-Makki Publisher, 2025)
The convergence of quantum computing threats and Zero Trust Architecture (ZTA) implementation presents unprecedented challenges for critical infrastructure protection. While quantum computers threaten current cryptographic foundations, Zero Trust frameworks require robust cryptographic mechanisms for continuous verification. This study examines the adaptation challenges and implementation strategies for integrating post-quantum cryptography within Zero Trust architectures across critical infrastructure sectors.A mixed-methods sequential explanatory design was employed with 147 critical infrastructure organizations across five sectors (energy, transportation, healthcare, financial services, telecommunications). Data collection included the Zero Trust Maturity Assessment Framework (ZTMAF), Post-Quantum Cryptography Readiness Index (PQCRI), Critical Infrastructure Vulnerability Assessment Protocol (CIVAP), semi-structured interviews (n=89), and document analysis (1,247 documents). Statistical analysis employed correlation analysis, ANOVA, and structural equation modeling, while qualitative data underwent thematic analysis.Zero Trust maturity varied significantly across sectors (M=2.91, SD=0.67), with financial services demonstrating highest maturity (M=3.81) and transportation lowest (M=2.50). Post-quantum cryptography readiness remained concerning across all sectors (M=2.47, SD=0.73), with only 16.3% achieving high readiness levels. Legacy systems prevalence (84.4% of organizations) negatively correlated with both ZTA maturity (r=-0.43) and PQC readiness (r=-0.58). Structural equation modeling revealed significant relationships between organizational factors and implementation success (x²/df=2.34, CFI=0.92).Critical infrastructure organizations face substantial challenges in quantum-safe Zero Trust implementation, with sector-specific barriers requiring targeted intervention strategies. The findings highlight urgent needs for government coordination, technical assistance programs, and accelerated legacy system modernization to ensure national cybersecurity resilience against emerging quantum threats.